Tuberculosis alters immune-metabolic pathways resulting in perturbed IL-1 responses - Llibre, Alba; Smith, Nikaïa; Rouilly, Vincent; Musvosvi, Munyaradzi; Nemes, Elisa; Posseme, Céline; Mabwe, Simbarashe; Charbit, Bruno; Mbandi, Stanley Kimbung; Filander, Elizabeth; Africa, Hadn; Saint-André, Violaine; et al. (Frontiers in Immunology, 2022)
Tuberculosis (TB) remains a major public health problem and we lack a comprehensive understanding of how Mycobacterium tuberculosis (M. tb) infection impacts host immune responses. We compared the induced immune response to TB antigen, BCG and IL-1β stimulation between latently M. tb infected individuals (LTBI) and active TB patients. This revealed distinct responses between TB/LTBI at transcriptomic, proteomic and metabolomic levels. At baseline, we identified a novel immune-metabolic association between pregnane steroids, the PPARγ pathway and elevated plasma IL-1ra in TB. We observed dysregulated IL-1 responses after BCG stimulation in TB patients, with elevated IL-1ra responses being explained by upstream TNF differences. Additionally, distinct secretion of IL-1α/IL-1β in LTBI/TB after BCG stimulation was associated with downstream differences in granzyme mediated cleavage. Finally, IL-1β driven signalling was dramatically perturbed in TB disease but was completely restored after successful treatment. This study improves our knowledge of how immune responses are altered during TB disease, and may support the design of improved preventive and therapeutic tools, including host-directed strategies.